2017
DOI: 10.3171/2016.8.spine16398
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral osteotomy of the pedicle and posterolateral elements for en bloc resection: a technique for oncological resection of posterolateral spinal tumors

Abstract: En bloc resection of tumors involving the spinal column is technically challenging and is associated with high morbidity to the patient due to the proximity of critical neurological and vascular structures and the destabilizing nature of this surgery. Nevertheless, evidence has shown improved progression-free survival with en bloc resection for certain low-grade malignant and aggressive benign musculoskeletal tumors. To avoid the morbidity of en bloc spondylectomy in patients with tumors localized to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Vasudeva et al. introduced COPPER as a novel surgical procedure ( 39 ). For this surgical procedure, laminectomies are performed above and below the tumor to reveal the dura, with a contralateral hemilaminectomy connecting them.…”
Section: Advances In Treatments For Spinal Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Vasudeva et al. introduced COPPER as a novel surgical procedure ( 39 ). For this surgical procedure, laminectomies are performed above and below the tumor to reveal the dura, with a contralateral hemilaminectomy connecting them.…”
Section: Advances In Treatments For Spinal Metastasismentioning
confidence: 99%
“…For patients with spinal metastases and a favorable PS, the absence of metastases to major organs, and tumors confined to the vertebral body, radical surgery including total en-bloc spondylectomy (TES), for complete removal of the tumor is preferred (35,37). Based on tumor localization, less invasive radical surgeries including sagittal en-bloc spondylectomy and contralateral osteotomy of the pedicle and posterolateral elements for en-bloc resection (COPPER) have also been reported (38)(39)(40).…”
Section: Advances In Treatments For Spinal Metastasismentioning
confidence: 99%
“…However, if localized to the posterior spine, en bloc resection will be complicated not only by the spinal cord and nerve root but also by pedicles. Vasudeva et al previously reported a case wherein contralateral osteotomy of the pedicle and posterolateral elements for en bloc resection (COPPER) was performed for a tumor localized posteriorly at one side 6 . However, COPPER cannot be indicated if the tumor is located on both sides of the posterior elements.…”
mentioning
confidence: 99%